Theoretical study of the mechanism behind the site- and enantio-selectivity of C–H functionalization catalysed by chiral dirhodium catalyst. Issue 17 (22nd April 2020) - Zhou, Meijuan; Springborg, Michael
Abstract : A detailed mechanism for the high site- and enantio-selectivity of C–H bond functionalization when using a chiral dirhodium catalyst is presented. Abstract : The C–H functionalization is very important for the synthesis of pharmaceuticals and complex natural products. Rhodium carbenoids, obtained when a dirhodium(ii ) catalyst containing a crown formed by chiral ligands reacts with diazo compounds with both an electron donating group and an electron withdrawing group, play an important part in controlling site- and enantio-selectivity for functionalization of non-activated C–H bonds. It has earlier been demonstrated that the tertiary C–H bond is more favored to be functionalized inside the crown of the dirhodium catalyst with S -configuration ligands compared with the secondary and primary C–H bonds although the latter possess weaker steric effects. We argue that the higher site- and enantio-selectivity for some types of C–H bond functionalization can be related to intermolecular hydrogen bonding, steric hindrance, and weak interactions when the dirhodium catalyst is interacting with the chiral ligands.